2000
DOI: 10.1046/j.1365-2273.2000.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Ossiculoplasty using hydroxyapatite prostheses: long-term results

Abstract: The surgical results of ossicular chain reconstruction using a hydroxyapatite prosthesis were evaluated in 106 ears of 101 patients who were followed up for > 5 years. Successful reconstruction was defined as: (1) postoperative air-bone gap of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 8 publications
2
27
0
2
Order By: Relevance
“…For reconstruction, multiple surgeries are often necessary and results are highly variable. Some evaluations of long-term results have indicated rates of failure of up to 45-50% for passive reconstruction using various materials, including extrusion rates up to 16% [Kapur and Jayaramchandran, 1992;Shinohara et al, 2000]. Despite fairly successful ossiculoplasties, hearing loss interfering with speech intelligibility remains in a substantial number of reconstruction patients, who require hearing aids even after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…For reconstruction, multiple surgeries are often necessary and results are highly variable. Some evaluations of long-term results have indicated rates of failure of up to 45-50% for passive reconstruction using various materials, including extrusion rates up to 16% [Kapur and Jayaramchandran, 1992;Shinohara et al, 2000]. Despite fairly successful ossiculoplasties, hearing loss interfering with speech intelligibility remains in a substantial number of reconstruction patients, who require hearing aids even after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A literature search revealed that of all available materials, hydroxyapatite (HA) was the most commonly used in the last decade [2]. However, long-term studies for HA alloplasts have reported an extrusion rate of 5-15% [3,4]. Present evidence indicates that titanium has a greater ability to transmit sound than the heavier HA [5].…”
Section: Introductionmentioning
confidence: 99%
“…Though a disk of cartilage between the head of prosthesis and tympanic membrane has reduced the risk of extrusion, cartilage disk did not eliminate it entirely [7]. Hydroxyapatite has been more successful as regards to functional hearing but extrusion rates remain high when used as TM-footplate assembly [8,9].…”
Section: Introductionmentioning
confidence: 99%